2017
DOI: 10.1002/mrm.26876
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach based on low‐field NMR for the detection of the pathological components of sputum in cystic fibrosis patients

Abstract: The presented method can potentially become a valuable lung-monitoring tool in CF patients. Magn Reson Med 79:2323-2331, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
5
20
0
Order By: Relevance
“…A further support for the relation between LF-NMR characterization and patients clinical conditions is provided by Figure 6 showing a linear correlation between T 2m and FEV1 (Forced Expiratory Volume in the first second), a typical test used to evaluate patients lung clinical conditions [21]. (ms)…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…A further support for the relation between LF-NMR characterization and patients clinical conditions is provided by Figure 6 showing a linear correlation between T 2m and FEV1 (Forced Expiratory Volume in the first second), a typical test used to evaluate patients lung clinical conditions [21]. (ms)…”
mentioning
confidence: 65%
“…Abrami et al [21] applied LF-NMR to establish a relation between the average relaxation time T 2m of the sputum of patients suffering from chronic obstructive pulmonary diseases (COPD, like cystic fibrosis) in relation to the patient's clinical conditions. This study was conducted by adopting the CPMG sequence set up described for the Figure 3 Figure 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in the sputum (derived from the lung mucus by expectoration) of CF patients, there is a pathological increase of the above biological elements with levels correlating to the severity of lung pathology . In our previous work, we showed that T 2m is able to detect the amounts of the pathological substances when dissolved in water (artificial sample) and in the saliva from healthy volunteers (conditional sputum) . These results prompted us to explore the possibility to measure T 2m also in the sputum of a large cohort of CF patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus evident that rapid, cost‐effective, and informative strategies for lung ventilation evaluation in CF patients are urgently required. We have recently developed a novel approach based on the measurement, by low field nucleic magnetic resonance (LF‐NMR), of the spin‐spin relaxation time ( T 2m ) of the water hydrogens present in a liquid solution. T 2m is influenced by the amount of different substances, such as proteins, biological polymers, and mucin, present in the liquid solution.…”
Section: Introductionmentioning
confidence: 99%